Grammatical aspect in Polish and the perception of event duration - Wojciech Milczarski (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Earlier research showed that the progressive aspect in Dutch extends duration estimations for short events and shortens the perception of inherently medium and long events. In the study reported here, we conducted an experiment examining whether the same effect can be observed in Polish, a language with a morphologically realised perfective vs. imperfective distinction. We confronted two views on grammatical aspect. The first one postulates that English simple past tense verbs of telic predicates introduce a silent PERF operator and that the Polish imperfective is equivalent to the English progressive. According to the second view, there is no PERF operator in simple past clauses in Dutch (and by analogy also in English), while perfective eventualities in Polish should be perceived as shorter than imperfective events which view the event from the inside without imposing any boundaries on its runtime. The results of this study show that the second view is more plausible, suggesting that languages vary in the interpretation of event duration depending on whether they have a clear grammatical aspect or whether such distinctions are less articulated.